2011
DOI: 10.1007/s13361-011-0210-0
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Family of Glycosylated Peptides Isolated from Dendroaspis angusticeps Venom and Characterized by Combination of Collision Induced and Electron Transfer Dissociation

Abstract: This study describes the structural characterization of a totally new family of peptides from the venom of the snake green mamba (Dendroaspis angusticeps). Interestingly, these peptides differ in several points from other already known mamba toxins. First of all, they exhibit very small molecular masses, ranging from 1.3 to 2.4 kDa. The molecular mass of classical mamba toxins is in the range of 7 to 25 kDa. Second, the new peptides do not contain disulfide bonds, a posttranslational modification commonly enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Recently, a proline-rich peptide was isolated from the venom of Dendroaspis angusticeps [54] which was described as being of an unknown peptide or protein type. The results of this study reveal that this proline-rich peptide is part of the propeptide region of the natriuretic peptide precursor, a fact missed by the aforementioned Dendroaspis study despite an Oxyuranus precursor being available that showed significant similarity to this peptide in an early stretch of the propeptide region.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a proline-rich peptide was isolated from the venom of Dendroaspis angusticeps [54] which was described as being of an unknown peptide or protein type. The results of this study reveal that this proline-rich peptide is part of the propeptide region of the natriuretic peptide precursor, a fact missed by the aforementioned Dendroaspis study despite an Oxyuranus precursor being available that showed significant similarity to this peptide in an early stretch of the propeptide region.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of Endogenous Glycoproteins-One interesting example of the need for characterization of biologically relevant, isolated glycoproteins is the analysis of several glycopeptides from the venom of Dendroaspis angusticeps (1). These highly active polypeptide compounds were found to be both glycosylated and rich in proline; both features are unusual in snake venom compounds.…”
Section: Because Epomentioning
confidence: 99%
“…These highly active polypeptide compounds were found to be both glycosylated and rich in proline; both features are unusual in snake venom compounds. Because the analytes of interest were generally under 4 kDa, no enzymatic digestion was required prior to analysis; and a top-down approach was used for assigning both the protein sequence, the glycosylation site occupancy, and the glycans themselves (1). The species contained small O-linked glycans.…”
Section: Because Epomentioning
confidence: 99%
See 2 more Smart Citations